AN ANALYSIS ON THE EFFECTS OF UNIVERSITIES IN NORTHERN CYPRUS ON THE POPULATION BEARING CAPACITY: ECOLOGIC THEORY. - İzzet Derkan , Tahir Vaiz (International Journal of Research Science and Management, 2018)
Due to the lack of a scientific study about the rapid increase of universities in Northern Cyprus in the recent years, the conformity of the demographic structure of the country to the '' Organizational Ecological Theory '' has become a subject of discussion. This aspect has attracted considerable attention to both the academicians and the living population. Due to the lack of articles written on this subject, the rate of increase in the number of universities in North Cyprus has not been studied scientifically. In this study, Northern Cyprus road network, crimes committed in Northern Cyprus, total number of vehicles and country population were examined. In the light of the obtained data, the universities that opened rapidly in Northern Cyprus exceed the carrying capacity of the country. Besides, many solutions have been reached during the interviews with the academicians. All this information can be found in this article. As a method, this study was conducted as a qualitative study supported by historical analysis, secondary sources and interviews. In conclusion, this study aimed to examine the increase of the universities in Northern Cyprus according